Effects of bark beetle attacks on forest snowpack and avalanche formation – Implications for protection forest management - Teich, Michaela; Giunta, Andrew D.; Hagenmuller, Pascal; Bebi, Peter; Schneebeli, Martin; Jenkins, Michael J. (Forest ecology and management, 2019)
•Snow penetration resistance was measured repeatedly below bark beetle killed trees.•Variability in snow stratigraphy was quantified with a new layer matching algorithm.•Spatial variability in snow stratigraphy is driven by percentage of canopy cover.•Leaving dead trees in protection forests contributes to avalanche protection.•Salvage logging can result in snow stratigraphy more prone to avalanche release. Healthy, dense forests growing in avalanche terrain reduce the likelihood of slab avalanche release by inhibiting the formation of continuous snow layers and weaknesses in the snowpack. Driven by climate change, trends towards more frequent and severe bark beetle disturbances have already resulted in the death of millions of hectares of forest in North America and central Europe, affecting snowpack in mountain forests and potentially reducing their protective capacity against avalanches. We examined the spatial variability in snow stratigraphy, i.e., the characteristic layering of the snowpack, by repeatedly measuring vertical profiles of snow penetration resistance with a digital snow micro penetrometer (SMP) along 10- and 20-m transects in a spruce beetle-infested Engelmann spruce forest in Utah, USA. Three study plots were selected characterizing different stages within a spruce beetle outbreak cycle: non-infested/green, infested > 3 years ago/gray stage, and salvage-logged. A fourth plot was installed in a non-forested meadow as the control. Based on our SMP measurements and a layer matching algorithm, we quantified the spatial variability in snow stratigraphy, and tested which forest, snow and/or meteorological conditions influenced differences between our plots using linear mixed effects models. Our results showed that spatial variability in snow stratigraphy was best explained by the percentage of canopy covering a transect (R2 = 0.71, p < 0.001), and that only 14% of the variance was explained by the stage within the outbreak cycle. That is, differences between green and gray stage stands did not depend much on the reduction in needle mass, but spatial variability in snow stratigraphy increased significantly with increasing forest canopy cover. At both study plots, a more heterogeneous snow stratigraphy developed, which translates to disrupted and discontinuous snow layers and, therefore, reduced avalanche formation. We attribute this to the effect that small fine branches and twigs still present in the canopy of gray stage trees have on snow interception and unloading, and especially on canopy drip. In contrast, salvage logging that reduced the canopy cover to ∼25%, led to a spatially less variable and similar snow stratigraphy as observed in the meadow. At these two study plots, a homogeneous snow stratigraphy consisting of distinct vertical and continuous slope-parallel soft and hard snow layers including weak layers had formed, a condition which is generally more prone to avalanche release. Our findings therefore emphasize advantages of leaving dead trees in place, especially in protection forests where bark beetle populations have reached epidemic levels.